Representasi Budaya Patriarki dalam Serial Drama “Gadis Kretek” - Wahyuningratna, Ratu Nadya (Universitas Bina Sarana Informatika, 2024)
Patriarchal culture is very prevalent in indonesia, one of which is in the patrilineal Javanese culture. This culture seems to portray women as objects and do not have the dominance of men. drama series have become one of the effective mass communications that have long been a forum for voicing social issues, one of which is about the patriarchal culture that occurs in society. A drama series that recently aired on Netflix, namely Gadis Kretek, is one of the works that raises this issue. Set in a region in Java in the 60s, at that time issues regarding patriarchal culture were very close considering the role of Javanese women who had to